Dengue Virus Infects Primary Human Hair Follicle Dermal Papilla Cells - Wei, Kai-Che; Huang, Mei-Shu; Chang, Tsung-Hsien (Frontiers in Cellular and Infection Microbiology, 2018)
During the epidemic of dengue virus (DENV) infection in Taiwan in 2014 to 2015, we observed an abnormally high frequency of increased scalp hair shedding in infected individuals; that cannot be explained by telogen effluvium. In this study, the mechanism of DENV-caused hair loss was explored. Human hair-follicle dermal papilla cells (HFDPCs) are essential for hair follicle morphogenesis and cycling. Thus, we established an in vitro DENV infection model in HFDPCs. On immunofluorescence analysis, HFDPCs were susceptible to DENV infection, responded to type I interferon treatment against DENV and showed the antibody-dependent enhancement effect. The expression of the pro-inflammatory cytokines interleukin 6 and tumor necrosis factor  revealed an inflammatory response in DENV-infected HFDPCs. In particular, DENV infection impaired cell viability and activated caspase-associated cell death signaling in HFDPCs. In conclusion, DENV direct infection caused HFDPC inflammation and death; this might implicate the pathophysiology of hair loss after DENV infection. The knowledge of DENV infection of an immune-privileged tissue, such as hair follicles, may suggest their use for further study of post-dengue syndrome.